Comparison of Effectiveness of Menstrual Regulation by Medication up to 6 Weeks of Gestation & 7-9 Weeks of Gestation (Ibrahim Cardiac Medical Journal, 2017)
Objective: The present study was undertaken to compare the effectiveness of menstrual regulation (MR) by medication (mifepristone and misoprostol) between women up to 6 weeks and 7-9 weeks of gestation.Method: This prospective study was carried out in the Department of Obstetrics & Gynaecology, Dhaka Medical College Hospital, Dhaka, over a period of 6 months from August 2014 to January 2015. Women seeking menstrual regulation (MR) services with gestational age no more than 9 weeks and confirmed intrauterine pregnancy attending at Reproductive Health Services Training and Education Program (RHSTEP) & Gynaecology Outpatient Department of Dhaka Medical College Hospital were taken in the study. The patients were divided into two groups. One group consisted of women of gestational age up to 42 days, known as early MR (Group-I, n = 41) and another group consisted of women of gestational age 43-63 days termed late MR (Group-II, n = 42). The main outcome variables were time to bleeding following intervention, complete abortion and need for secondary intervention.Result: The demographic characteristics like age, socioeconomic status, level of education and occupation were almost identically distributed between groups. The women of the two groups were almost matched in terms of their gravidity, past history of abortion or MR, use of contraceptive and indication of present MR. Time to bleeding following misoprostol administration was on an average 2 and a ½ hours and there was no significant difference between the groups (p = 0.804). Over half (51.2%) of the women up to 42 days of gestation completed abortion at or before 1st follow up visit as opposed to only 19% in late gestation group (p = 0.002). The need for 2nd dose misoprostol to complete the abortion was significantly higher in the latter group than that in the former group (p < 0.001). The need for surgical intervention (for delayed, heavy bleeding) was comparatively less in the former group. Muscle cramping and nausea/vomiting were the most noted complications and were considerably higher in the former group. Women in the early gestation group more often reported (17.1%) less bleeding following intervention compared to that reported by the women of late gestation (2.4%) (p = 0.038). However, pain, adverse effect and time to complete the procedure all were acceptable to the majorities of women of either group.Conclusion: The study concluded that Menstrual Regulation with Medication (MRM) with misoprostol is effective in aborting the uterine content in women with early gestation with less bleeding and other complications. As the bleeding is more in women with late gestation, universal recommendation of its use to women with late gestation may be risky.Ibrahim Card Med J 2015; 5 (1&2): 21-26